2014
DOI: 10.5455/gmj-30-154373
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and behavior about breast cancer in women presenting to Early Cancer Diagnosis, Screening and Education Centre in Kahramanmaras, Turkey

Abstract: This study was performed to investigate knowledge, attitudes and behavior about breast cancer in the women applying to Early Cancer Diagnosis, Screening and Education Centre. The study included 96 women applying to Early Cancer Diagnosis, Screening and Education Centre between 1 January 2013 and 1 February 2014. The women were offered information about the study and those giving written informed consent were enrolled in the study. A questionnaire created by the researchers was used to collect data. The mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“… 5 - 7 Despite this finding, low participation rates in BC screening activities have been reported among Arab women. 6 , 8 - 10 Breast cancer is reported from developed nations and Western countries, while data on relevant reports from KSA appears either scattered, or not brought to the limelight. 11 Regarding risk factors, women with a family history of BC should obtain as much information as possible on those relatives, including age at onset, and type of cancer.…”
mentioning
confidence: 99%
“… 5 - 7 Despite this finding, low participation rates in BC screening activities have been reported among Arab women. 6 , 8 - 10 Breast cancer is reported from developed nations and Western countries, while data on relevant reports from KSA appears either scattered, or not brought to the limelight. 11 Regarding risk factors, women with a family history of BC should obtain as much information as possible on those relatives, including age at onset, and type of cancer.…”
mentioning
confidence: 99%
“…This is emphasized in order to increase the effectiveness of the screening methods, it is needed to use two or three of the methods in combination. However, in this regard, studies published in many countries and in Turkey have shown that the rate of participation of women in the BC screening program was low (6)(7)(8)(9)(10)(11)(12)(13). The reasons why women did not participate in the screening program included lack of information and pain ranking the first, not wanting to be exposed to radiation, being afraid to discover the cancer, embarrassment, fatalism, and misinformation, not seeing a physician unless ill, possibility that screening might be refused by the family, negligence, lack of physician recommendation, health-care provider attitudes, not remembering to do it, discomfort, and having not enough time to handle it (12,(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Breast cancer is the most well-known cancer type (79%) and also most well-known that it could be detected early by screening among all cancer types (65.5%). Also in other studies, it was showed that patients knew breast cancer as the most common cancer, and they knew that breast cancer could be diagnosed early [13,14]. The most well-known sign of cancer was weight loss (62.8%) followed by fatigue (58%) and mass (swelling) (%53.8).…”
Section: Discussionmentioning
confidence: 97%
“…The studies performed about this subject either studied only one type of cancers or were assessing the attitudes of doctors about cancer screenings [11][12][13][14][15]. Also these studies generally were performed locally.…”
Section: Discussionmentioning
confidence: 99%